An improved SPH model for turbulent hydrodynamics of a 2D oscillating water chamber. (15th February 2018) - Wen, Hongjie; Ren, Bing; Yu, Xiping
Abstract: An improved smoothed particle hydrodynamic (SPH) model is developed to study the complex hydrodynamic behaviour of an onshore oscillating water chamber. The improvements include adding a diffusive term to the continuity equation and incorporating the corrective smoothed particle method (CSPM). A modified boundary condition is implemented to better simulate the pressure field near the solid boundary. The SPH model is first verified by comparing the numerical results with analytical solutions and the available experimental data. The verified model is then applied to study the hydrodynamic behaviour of an onshore oscillating water chamber. The free surface elevations inside the water chamber and the total forces acting on the front wall of the water chamber are studied for different wave conditions. The turbulence energy distribution and the sloshing phenomenon in the water chamber are also investigated. Highlights: Performance of SPH model is enhanced through several modified methods. SPH model is verified by experimental data and analytical solutions. Hydrodynamics of the oscillating water chamber are analyzed.